Testing PCR amplification from elephant dung using silica-dried swabs - Andrew Tighe; Robert Gandola; Bernerd Fulanda; Kiera Thurman; Sarah Overby; John Byrne; Jens Carlsson (Pachyderm)
Swabbing scat samples is a simple, non-invasive method of obtaining DNA samples for population genetic analysis of wild elephants. In this study, swab samples were taken from the scat of African savanna elephants inhabiting the Galana Wildlife Conservancy (GWC), bordering Tsavo East National Park in south-east Kenya. The swab samples were dried with silica as opposed to traditional methods of preservation in liquid or freezing while in the field. Furthermore, this study examined the rate of DNA degradation in scat samples in semi-arid conditions, typical of the Galana Wildlife Conservancy, by repeated sampling of scat in the field following deposition at defined time intervals over a period of two weeks. Results showed that both nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) could be successfully amplified from scat samples up to 128 hours (about five days) following deposition. Significantly better results were obtained from samples taken from the outside of the scat than from the centre. Mitochondrial D-loop sequence data suitable for phylogenetic analysis was obtained from three fresh samples and one sample taken 16 hours after deposition. However, the sequence from a sample collected after 128 hours was not of sufficient quality for sequencing. Further research is required to determine at which point between 16 and 128 hours the DNA becomes too degraded for analysis. The mtDNA analysis showed the presence of the Southwest savanna subclade in two of the four samples from GWC, which has previously been found in only one other sample in Kenya. By confirming the effectiveness of silica-dried scat samples for use in DNA analysis, the results of this study will facilitate genetic analysis of African elephant populations and thereby contribute to efforts to conserve the gene pool of this keystone species. The paper contributes to the literature on collecting and preserving dung specimens with potential for conservation management.